2008
DOI: 10.1002/jctb.1895
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Aspergillus carbonarius polygalacturonase using polymeric membranes

Abstract: BACKGROUND: Microfiltration (MF: 70-450 nm) and ultrafiltration (UF: 10-500 kDa) membranes were used to eliminate carbohydrates and other non-protein impurities from Aspergillus carbonarius culture broth containing polygalacturonase enzyme (EC 3.2.1.15) that would otherwise interfere with the purification processes and lead to enzyme loss. Further, diafiltration was attempted to improve the elimination of impurities as well as recovery of enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Earlier experiments using several UF membranes (10, 25, 100, and 500 kDa) showed that the 10 kDa membrane in diafiltration operation removed most of the carbohydrates, phosphate salts, and total acids from A. carbonarius culture broth with a higher PG recovery [11]. Although the protocol was effective in eliminating non-protein impurities, there was practically no improvement in the enzyme specific activity since contaminating proteins were also recovered along with the enzyme.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Earlier experiments using several UF membranes (10, 25, 100, and 500 kDa) showed that the 10 kDa membrane in diafiltration operation removed most of the carbohydrates, phosphate salts, and total acids from A. carbonarius culture broth with a higher PG recovery [11]. Although the protocol was effective in eliminating non-protein impurities, there was practically no improvement in the enzyme specific activity since contaminating proteins were also recovered along with the enzyme.…”
Section: Resultsmentioning
confidence: 85%
“…membranes ( Table 3). The first two steps were employed for pre-processing the crude culture broth to eliminate non-protein impurities as described earlier [11]. Processing the above culture broth after suitable dilution through 450 nm MF membrane eliminated 21% larger contaminating proteins.…”
Section: Purification Of Pg (Cf-uf-mf-uf)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in spite of widespread use of ultrafiltration in processes such as diafiltration and concentration, the potential for its use in protein fractionation has not been exploited in the biotechnology industry [17]. Nevertheless, there are studies that show that ultrafiltration can be applied to purification of enzymes, obtaining high yields and product purity at the same time [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Although a lot of recent studies have demonstrated the possibility of proteins fractionation by UF, some of them dealt with simulated binary or ternary mixtures [29,30]. Experimental studies of real biological streams are not very often presented [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%